Targeted grants allocated from the state budget as a source of financing local government investments - Piszczek, Marzena (Dotacje z budżetu państwa jako źródło finansowania inwestycji samorządowych, 2019)
Financing investments is one the most important issues in the policy of local governments. One of the ways of supporting local governments are targeted grants for investments from the state budget. Recent years have been characterized by a change in the policy of financing local governments in this area, which was mainly related to the change of priorities from investment to social policy support. The aim of the article is to present the legal possibilities and actual use of available sources of financing local and regional development by local governments units coming from targeted grants from the state budget of an investment character in the period of 2014-2018
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 10, s. 74-85